Optimal Timing of Delayed Microvascular Breast Reconstruction after Radiation Therapy - Arnautovic, Aska; Karinja, Sarah; Olafsson, Soley; Carty, Matthew J.; Erdmann-Sager, Jessica; Caterson, Stephanie A.; Broyles, Justin M. (Journal of Reconstructive Microsurgery, 2022)
Background The purpose of this study was to determine the optimal timing of delayed microvascular breast reconstruction after completion of postmastectomy radiation therapy (PMRT). The authors evaluated whether the timing of reconstruction after PMRT completion affects the development of major postoperative complications. We hypothesize that delayed microvascular breast reconstruction can be safely performed within 12 months of PMRT completion.Methods A retrospective chart review of microvascular, autologous breast reconstructions at Brigham and Women's Hospital from 2007 to 2019 was performed. Logistic regression analysis and marginal estimation methods were used to estimate the probability of any major complication (flap compromise requiring operative intervention, hematoma formation requiring evacuation, infection requiring readmission, and flap necrosis requiring operative debridement) occurring in 2-month intervals after PMRT. Patients were classified as having undergone reconstruction 0 to 12 months after PMRT (group 1), 12 to 18 months after PMRT (group 2), or 18 to 50 months after PMRT (group 3).Results A total of 303 patients were identified. All patients received postmastectomy radiation (n = 143 group 1, n = 57 group 2, n = 103 group 3). Mean follow-up time was 71.4 ± 38 months. Patients in group 1 were significantly younger and more likely to have undergone neoadjuvant chemotherapy (p < 0.05). Major complications occurred in 10% of patients. There was no significant difference in the development of major complications between the three groups (p = 0.57). Although not statistically significant, the probability of any major complication peaked 2 to 6 months after PMRT completion.Conclusion There was no significant difference in major complications among patients who underwent delayed, microvascular breast reconstruction within versus beyond 1 year of PMRT completion. These findings suggest that delayed microvascular breast reconstruction can be safely performed beginning 6 months after PMRT completion.
Keywords: reconstructive timing; microvascular breast reconstruction